THE USING OF PANTOMIME TO IMPROVE THE STUDENTS' SPEAKING SKILL - Sulton, Achmad (Departemen Pendidikan Bahasa, Fakultas Ilmu Budaya, Universita Brawijaya, 2021)
Abstract:The purpose of this classroom action research is to improve the students’ speaking skill by using Pantomime, it is also to share toward the teachers the new media of teaching and learning in the classroom. This action research is the research that has been done in two cycles. Cycle one consists of three meeting while cycle two consists of two meeting. It is done in the tenth grade of State Senior High School 4 Malang. There are thirty three students in it. The result of this classroom action research shows that the using of Pantomime can improve the students' speaking skill.Abstract: Tujuan penelitian tindakan kelas adalah meningkatkan keahlian murid dalam berbicara dengan menggunakan Pantomim, berbagi dengan guru-guru yang lain tentang penggunaan media pembelajaran Pantomim. Penelitian tindakan kelas ini dilaksanakan dalam 2 siklus. Siklus pertama terdiri dari tiga pertemuan sedangkan siklus kedua terdiri dari dua pertemuan. Penelitian ini dilakukan dikelas X SMA Negeri 4 Malang.subject penelitiannya adalah 33 murid. Hasil dari penelitian ini menunjukkan bahwa penggunaan Pantomim dapat meningkatkan keahlian murid dalam berbicara.